HUBUNGAN PENGGUNAAN ALAT PELINDUNG DIRI (APD) DENGAN KETERPAPARAN LOGAM TIMBAL (Pb) PADA PETUGAS TANDA PEMBAYARAN RETRIBUSI (TPR) DINAS PERHUBUNGAN DI TERMINAL RAJABASA BANDAR LAMPUNG: THE RELATIONSHIP OF THE USE OF SELF-PROTECTIVE EQUIPMENT (EXTENSION) WITH EXPOSURE OF TIMBAL (PB) IN RETRIBUTION SIGN OFFICERS OF DEPARTMENT OF TRANSPORTATION IN RAJABASA TERMINAL BANDAR LAMPUNG - Sari, nova Nurwinda; Putri, Lentera Nunyai; Agata, Annisa (Bali Medika Jurnal, 2019)
Transportation contributes more than half of the causes of air pollution, especially from vehicles that use gasoline as fuel. The Transportation Department's levy payment (TPR) duty officer at Rajabasa Bandar Lampung terminal has a risk of lead metal exposure (Pb). The impact of lead metal exposure (Pb) can attack the nervous system, kidney system, reproductive system, endocrine system, and heart. This type of quantitative research is an observational analytic method with cross sectional design. The population amounted to 36 officers of payment levy (TPR) of the Department of Transportation at the terminal Rajabasa Bandar Lampung. The sample is the total population of blood samples of officers. Instruments used binocular microscope and measurement method of Blood Screen Preparation with the discovery of basophilic stippling cells. Data analysis used univariate and bivariate test Fisher Exact. Based on univariate test result 25 respondents (69,4%) exposed positively exposed to lead metal (Pb) and statistical test obtained Fisher Exact (p value >0,05) meaning that there is not relation between usage of personal protective equipment (APD) with exposure of metal lead (Pb) to the officer of payment levy (TPR) of the transportation agency at the terminal of Rajabasa Bandar Lampung.